Analisis Metode Pembelajaran Observasi dalam Pembelajaran Menulis Puisi Terhadap Motivasi Belajar Siswa Kelas VIII SMPN 20 Malang - Sari, Adel Lia Novita; Yuliasari, Lina; Abadi, Machrus (Pedagogika: Jurnal Ilmu-Ilmu Kependidikan, 2024)
Learning methods certainly have a great influence on students' learning motivation in mastering certain competencies, one of which is the competence of writing poetry in grade VIII junior high school students. This study aims to find out the method of observation learning in learning to write poetry on the learning motivation of grade VIII students at SMPN 20 Malang. The data source used is grade VIII students of SMPN 20 Malang. This research is a qualitative descriptive research with qualitative research methods. The data collection method was carried out by observation and interviews. Data analysis is carried out by identifying, analyzing, and inferring data. The results of this study are in the form of a description of the analysis of observation learning methods in learning to write poetry on the learning motivation of grade VIII students at SMPN 20 Malang.